2013
DOI: 10.5194/amt-6-471-2013
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical depth (AOD) retrieval using simultaneous GOES-East and GOES-West reflected radiances over the western United States

Abstract: Abstract. Aerosol optical depth (AOD) in the western United States is observed independently by both the (Geostationary Operational Environmental Satellites) GOES-East and GOES-West imagers. The GASP (GOES Aerosol/Smoke Product) aerosol optical depth retrieval algorithm treats each satellite as a unique sensor and thus obtains two separate aerosol optical depth values at the same time for the same location. The TOA (the top of the atmosphere) radiances and the associated derived optical depths can be quite dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The improvement of AOD is in part due to the much lower surface reflectance in the near-UV (where TEMPO measures) and is especially evident when TEMPO is located in the zenith direction of the sun, the direction for which the surface bidirectional reflectance distribution function (BRDF) is largest (J. [116,123]). Multiple measurements taken for the same pixel (from same viewing angle but multiple solar zenith angle and therefore scattering angles) can provide information on aerosol shape [118].…”
Section: Trace Gas Column Measurementsmentioning
confidence: 99%
“…The improvement of AOD is in part due to the much lower surface reflectance in the near-UV (where TEMPO measures) and is especially evident when TEMPO is located in the zenith direction of the sun, the direction for which the surface bidirectional reflectance distribution function (BRDF) is largest (J. [116,123]). Multiple measurements taken for the same pixel (from same viewing angle but multiple solar zenith angle and therefore scattering angles) can provide information on aerosol shape [118].…”
Section: Trace Gas Column Measurementsmentioning
confidence: 99%
“…After several studies suggested that the surface reflectance relationships in the VIS and 2.1 µm bands were angle (4). NDVI SWIR is an aerosol resistant measure of vegetation "greenness," defined in Equation (5).…”
Section: Theoretical Basis Of Aod Retrievalmentioning
confidence: 99%
“…Aerosols can absorb or scatter the incoming solar radiation and affect the Earth's radiation budget, thus modulating the warming or cooling of the Earth [2,3]. Ground-level aerosols, also known as particulate matter (PM), are associated with human health and as such are regulated as a priority air quality pollutant [4,5]. Aerosol monitoring contributes significantly to the understanding of the Earth's environmental systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of another Asian geostationary satellite, the Multi-functional Transport Satellite (MTSAT-1R), visible and mid-IR channels were used in the AOD retrieval [12]. For the western hemisphere, measurements are made by the Geostationary Operational Environmental Satellite (GOES), for which an AOD retrieval algorithm was presented by Zhang et al [13], and recently a new version of the algorithm that uses data from two geostationary satellites, GOES-West and GOES-East [14], was developed.…”
Section: Introductionmentioning
confidence: 99%